An Efficient Hairy Root System for Validation of Plant Transformation Vector and CRISPR/Cas Construct Activities in Cucumber (Cucumis sativus L.) - Nguyen, Doai Van; Hoang, Trang Thi-Huyen; Le, Ngoc Thu; Tran, Huyen Thi; Nguyen, Cuong Xuan; Moon, Yong-Hwan; Chu, Ha Hoang; Do, Phat Tien (Frontiers in Plant Science, 2022)
Hairy root induction system has been applied in various plant species as an effective method to study gene expression and function due to its fast-growing and high genetic stability. Recently, these systems have shown to be an effective tool to test activities of CRISPR/Cas9 systems for genome editing. In this study, Rhizobium rhizogenes mediated hairy root induction was optimized in order to provide an effective tool for validation of plant transformation vector, CRISPR/Cas9 construct activities as well as selection of targeted gRNAs for gene editing in cucumber (Cucumis sativus L.). Under the optimized conditions including OD650 at 0.4 for infection and five days of co-cultivation, the highest hairy root induction frequency reached 100% for the cucumber variety Choka F1. This procedure was successfully utilized to overexpress a reporter gene (gus) and induce mutations in two Lotus japonicus ROOTHAIRLESS1 homolog genes CsbHLH66 and CsbHLH82 using CRISPR/Cas9 system. For induced mutation, about 78% of transgenic hairy roots exhibited mutant phenotypes including sparse root hair and root hair-less. The targeted mutations were obtained in individual CsbHLH66, CsbHLH82 or both CsbHLH66 and CsbHLH82 genes by heteroduplex analysis and sequencing. The hairy root transformation system established in this study is sufficient and potential for further researches in genome editing of cucumber as well as other cucumis plants.